The possession [videorecording (DVD)] - Bornedal, Ole; Sedgwick, Kyra; Morgan, Jeffrey Dean, 1966-; Brazeau, Jay, 1953- (Lionsgate, 2013)
Clyde and Stephanie Brenek see little cause for alarm when their youngest daughter Em becomes oddly obsessed with an antique wooden box she purchased at a yard sale. But as Em's behavior becomes increasingly erratic, the couple fears the presence of a malevolent force in their midst, only to discover that the box was built to contain a Dibbuk, a dislocated spirit that inhabits and ultimately devours its human host.